The First Case of Ischemia-Free Kidney Transplantation in Humans - He, Xiaoshun; Chen, Guodong; Zhu, Zebin; Zhang, Zhiheng; Yuan, Xiaopeng; Han, Ming; Zhao, Qiang; Zheng, Yitao; Tang, Yunhua; Huang, Shanzhou; Wang, Linhe; van Leeuwen, Otto B.; et al. (Frontiers in Medicine, 2019)
Background. Ischemia-reperfusion injury (IRI) has been considered an inevitable event in organ transplantation since the first successful kidney transplant was performed in 1954. To avoid IRI, we have established a novel procedure called ischemia-free organ transplantation. Here, we describe the first case of ischemia-free kidney transplantation (IFKT). Meterials and methods. The kidney graft was donated by a 19-year-old brain dead donor. The recipient was a 47-year-old man with end-stage diabetic nephropathy. The graft was procured, preserved and implanted without cessation of blood supply using normothermic machine perfusion. Results. The graft appearance, perfusion flow and urine production suggested the kidney was functioning well during the whole procedure. The creatinine dropped rapidly to normal range within three days post-transplantation. The levels of serum renal injury markers were low post-transplantation. No rejection, vascular or infectious complications occurred. The patient had an uneventful recovery. Conclusion. This paper marks the first case of IFKT in humans. This innovation might offer a unique solution to optimize transplant outcomes and overcome organ shortage in kidney transplantation.